The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/sdi.12806
|View full text |Cite
|
Sign up to set email alerts
|

The role of exercise in improving patient‐reported outcomes in individuals on dialysis: A scoping review

Abstract: Exercise improves objective measures of physical function in individuals on hemodialysis, but its effect on patient‐reported outcomes (PROs) is largely unknown. We performed a scoping review to characterize the existing knowledge base on exercise and PROs in dialysis patients to make recommendations for future research. We searched Medline, Embase, Cochrane Database of Systematic Reviews; Cochrane Central Register of Controlled Trials, CINAHL, and SPORT Discus from inception to November 28, 2018 and then scree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 43 publications
0
14
0
1
Order By: Relevance
“…However, reduction in QOL was not observed in their female cohort. A small randomized controlled trial by Dziubek et al [100] found that physical training and exercise in men and women receiving HD significantly reduced depression and anxiety, and a review by Bohm et al [101] showed that longer exercise duration (>6 months) in dialyzing adults was correlated with a significant improvement in symptoms of depression.…”
Section: Depression Anxiety and Quality Of Lifementioning
confidence: 99%
“…However, reduction in QOL was not observed in their female cohort. A small randomized controlled trial by Dziubek et al [100] found that physical training and exercise in men and women receiving HD significantly reduced depression and anxiety, and a review by Bohm et al [101] showed that longer exercise duration (>6 months) in dialyzing adults was correlated with a significant improvement in symptoms of depression.…”
Section: Depression Anxiety and Quality Of Lifementioning
confidence: 99%
“…To the best of our knowledge, it currently remains unknown whether exercise interventions have a similar effect in CKD/ESKD patients. However, exercise therapy was recently suggested to improve physical function [95,96] and other symptoms, including restless legs syndrome [97], in dialysis patients. Even if the effects of exercise on constipation are not sufficient, habitual exercise is associated with other beneficial effects.…”
Section: Lifestyle-based Therapymentioning
confidence: 99%
“…Moreover, Gopaluni et al 17 , concluded in their review that additional studies are required to investigate the effect of exercise programs with intradialytic intervention in the improvement of sleep disorders. In a recent review, Bohm et al 18 also demonstrated few studies with intradialytic exercise and sleep quality. Also, part of these studies had as primary outcome glycemic and/or lipid homeostasis.…”
Section: Introductionmentioning
confidence: 99%